PENGUATAN MODERASI BERAGAMA DALAM MEMBENTUK KARAKTER SISWA DI MADRASAH ALIYAH RAUSHAN FIKRI ISLAMIC SCHOOL LANGKAT-SUMATERA UTARA - Al Farabi, Mohammad (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
This study aims to analyze the educational process which contains the strengthening of religious moderation in shaping the character of students at Madrasah Aliyah Raushan Fikri Islamic School. This research was conducted in the form of field research using qualitative methods and Miles-Huberman analysis techniques, namely data reduction, data presentation, and conclusions. By conducting observations, interviews, and document studies, it was found that strengthening religious moderation at Madrasah Aliyah Raushan Fikri Islamic School was carried out by internalizing the values of religious moderation in several subjects, implementing the integration of knowledge in the learning process, applying it in daily interactions in schools, developing a tradition of religious literacy, and at certain times students are directed to take part in activities based on religious moderation